2013
DOI: 10.1186/1747-597x-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-assessed increase in tobacco consumption among over-indebted individuals in Germany: a cross-sectional study

Abstract: BackgroundOver-indebtedness is an increasing phenomenon in industrialised nations causing individual hardship and societal problems. Nonetheless, few studies have explored smoking among over-indebted individuals.MethodsA cross-sectional survey (n=949) on retrospectively assessed changes in tobacco consumption was carried out in 2006 and 2007 among clients of 84 officially approved debt and insolvency counselling centres in Germany (response rate 39.7%). Logistic regressions were performed to explore factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As a result, it is not surprising that most smoking cessation interventions have been largely ineffective for adults who experience hardships. 22,[37][38][39][40] Additionally, a recent study has noted that maternal smokers reporting more smoke-related child sick visits, greater perceived life stress, and less social support were more likely to report significant depressive symptoms than mothers with fewer clinic visits, less stress, and greater social support. 41 Stress, depression, and hardships may affect child exposure levels and health, and depression may be another area for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is not surprising that most smoking cessation interventions have been largely ineffective for adults who experience hardships. 22,[37][38][39][40] Additionally, a recent study has noted that maternal smokers reporting more smoke-related child sick visits, greater perceived life stress, and less social support were more likely to report significant depressive symptoms than mothers with fewer clinic visits, less stress, and greater social support. 41 Stress, depression, and hardships may affect child exposure levels and health, and depression may be another area for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Over-indebtedness may be associated with not being able to consume health-enhancing food and services, to access healthcare and to fully participate in social life (Goode, 2012b; see also Münster et al, 2009;Averett and Smith, 2014). A cross-sectional survey among clients of officially approved debt and insolvency counselling centres in Germany identified over-indebted individuals, and particularly over-indebted men, as a high-risk group of smokers (Rueger et al, 2013). Studies from Finland showed that over-indebtedness was also associated with the incidence of chronic disease, including severe depression, in a follow-up setting (Blomgren et al, 2016(Blomgren et al, , 2017.…”
Section: Mental Health and Physical Healthmentioning
confidence: 99%
“…People with serious debt problems and in severe economic difficulties experience psychological distress [ 13 ], poor self-reported health [ 14 ], mental ill health or mental disorders and particularly depression [ 2 , 3 , 7 , 8 , 15 19 ], sleep problems [ 20 , 21 ], chronic diseases such as hypertension or diabetes [ 2 , 7 ], overweight and obesity [ 4 ] and back pain or pain in general [ 5 , 22 ]. Over-indebted individuals also show higher risks of self-destructive behaviors such as suicidal behavior [ 8 , 19 ], smoking [ 6 , 23 ], alcohol and drug abuse [ 18 , 19 ] or problem gambling [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%